2017
DOI: 10.1371/journal.pone.0178677
|View full text |Cite
|
Sign up to set email alerts
|

Trends of vaccine-preventable diseases in Afghanistan from the Disease Early Warning System, 2009–2015

Abstract: BackgroundAfghanistan’s public health system was neglected during decades of military and civil conflict, and trends in infectious disease occurrence remain poorly characterized. This study examines cyclical and long-term trends of six vaccine-preventable diseases: pneumonia, diarrhea, meningitis, typhoid, measles, and acute viral hepatitis.MethodsUsing weekly data collected between 2009 and 2015 through Afghanistan’s Disease Early Warning System, we calculated monthly case counts, and fit a Poisson regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
9
2
Order By: Relevance
“…There was also a significant difference in the season in which the diseases were contracted; typhoid cases tended to rise in the fall and winter, whereas paratyphoid cases increased in the spring and summer. A previous study [22] found that the greatest incidence of diarrhea and typhoid occurred in the summer; this result is not similar to that of this study. This study suggested that the different prevalences of typhoid in the different seasons may have occurred due to the differences in hygiene or culture between Taiwan and Afghanistan.…”
Section: Discussioncontrasting
confidence: 99%
“…There was also a significant difference in the season in which the diseases were contracted; typhoid cases tended to rise in the fall and winter, whereas paratyphoid cases increased in the spring and summer. A previous study [22] found that the greatest incidence of diarrhea and typhoid occurred in the summer; this result is not similar to that of this study. This study suggested that the different prevalences of typhoid in the different seasons may have occurred due to the differences in hygiene or culture between Taiwan and Afghanistan.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there have been instances of outbreak of vaccine preventable diseases in countries like Pakistan, Malaysia, Nepal, and Egypt . [43][44][45] This would emphasize the fact that cultural factors may be more influential rather than limited knowledge and negative attitude toward vaccination. 44,46 Our study reflected that the majority of the vaccine compliant mothers are educated.…”
Section: Attitude Of Mothers Toward Vaccinationmentioning
confidence: 99%
“…Child mortality is higher in Afghanistan compared with other countries [12]. Afghanistan has poor health indicators, based on data from 2015, and was reported as one of the most dangerous countries for children, with one of every 18 children dying before reaching their first year [13].…”
Section: Introductionmentioning
confidence: 99%